Seasonal soil and leaf CO2 exchange rates in a Mediterranean holm oak forest and their responses to drought conditions - Asensio, Dolores; Penuelas, Josep; Ogaya, Romà; Llusia, Joan (ATMOSPHERIC ENVIRONMENT, 2007)
We measured the soil and leaf CO2 exchange in Quercus ilex and Phillyrea latfolia seasonally throughout the year in a representative site of the Mediterranean region, a natural holm oak forest growing in the Prades Mountains in southeastern Catalonia. In the wet seasons (spring and autumn), we experimentally decreased soil moisture by 30%, by excluding rainfall and water runoff in 12 plots, 1 x 10 m, and left 12 further plots as controls. Our aim was to predict the response of these gas exchanges to the drought forecasted for the next decades for this region by GCM and ecophysiological models. Annual average Soil CO2 exchange rate was 2.27 +/- 0.27 mu mol CO2 m(-2) s(-1). Annual average leaf CO2 exchange rates were 8 +/- 1 and 5 +/- 1 mu mol m(-2) s(-1) in Q. ilex and P. latfolia, respectively. Soil respiration rates in control treatments followed a seasonal pattern similar to photosynthetic activity. They reached maximum values in spring and autumn (2.5-3.8 mu mol m(-2) s(-1) soil CO2 emission rates and 7-15 mu mol m(-2) s(-1) net photosynthetic rates) and minimum values (almost 0 for both variables) in summer, showing that soil moisture was the most important factor driving the soil microbial activity and the photosynthetic activity of plants. In autumn, drought treatment strongly decreased net photosynthesis rates and stomatal conductance of Q. ilex by 44% and 53%, respectively. Soil respiration was also reduced by 43% under drought treatment in the wet seasons. In summer there were larger soil CO2 emissions in drought plots than in control plots, probably driven by autotrophic (roots) metabolism. The results indicate that leaf and Soil CO2 exchange may be strongly reduced (by ca. 44%) by the predicted decreases of soil water availability in the next decades. Long-term studies are needed to confirm these predictions or to find out possible acclimation of those processes. (c) 2006 Elsevier Ltd. All rights reserved.
The following values have no corresponding Zotero field: pub-location: THE BOULEVARD, LANGFORD LANE, KIDLINGTON, OXFORD OX5 1GB, ENGLAND publisher: PERGAMON-ELSEVIER SCIENCE LTD
Keywords: climate change; Drought; foliar net photosynthetic rates; Mediterranean holm oak forest; microorganisms; roots; soil CO2 exchange

Seasonal soil and leaf CO2 exchange rates in a Mediterranean holm oak forest and their responses to drought conditions (ATMOSPHERIC ENVIRONMENT, 2007)
We measured the soil and leaf CO2 exchange in Quercus ilex and Phillyrea latfolia seasonally throughout the year in a representative site of the Mediterranean region, a natural holm oak forest growing in the Prades Mountains in southeastern Catalonia. In the wet seasons (spring and autumn), we experimentally decreased soil moisture by 30%, by excluding rainfall and water runoff in 12 plots, 1 x 10 m, and left 12 further plots as controls. Our aim was to predict the response of these gas exchanges to the drought forecasted for the next decades for this region by GCM and ecophysiological models. Annual average Soil CO2 exchange rate was 2.27 +/- 0.27 mu mol CO2 m(-2) s(-1). Annual average leaf CO2 exchange rates were 8 +/- 1 and 5 +/- 1 mu mol m(-2) s(-1) in Q. ilex and P. latfolia, respectively. Soil respiration rates in control treatments followed a seasonal pattern similar to photosynthetic activity. They reached maximum values in spring and autumn (2.5-3.8 mu mol m(-2) s(-1) soil CO2 emission rates and 7-15 mu mol m(-2) s(-1) net photosynthetic rates) and minimum values (almost 0 for both variables) in summer, showing that soil moisture was the most important factor driving the soil microbial activity and the photosynthetic activity of plants. In autumn, drought treatment strongly decreased net photosynthesis rates and stomatal conductance of Q. ilex by 44% and 53%, respectively. Soil respiration was also reduced by 43% under drought treatment in the wet seasons. In summer there were larger soil CO2 emissions in drought plots than in control plots, probably driven by autotrophic (roots) metabolism. The results indicate that leaf and Soil CO2 exchange may be strongly reduced (by ca. 44%) by the predicted decreases of soil water availability in the next decades. Long-term studies are needed to confirm these predictions or to find out possible acclimation of those processes. (c) 2006 Elsevier Ltd. All rights reserved.